Inflammatory Markers, Pulmonary Function, and Clinical Symptoms in Acute COVID-19 Among Non-Hospitalized Adolescents and Young Adults - Lund Berven, Lise; Selvakumar, Joel; Havdal, Lise; Stiansen-Sonerud, Tonje; Einvik, Gunnar; Leegaard, Truls Michael; Tjade, Trygve; Michelsen, Annika E.; Mollnes, Tom Eirik; Wyller, Vegard Bruun Bratholm (Frontiers in Immunology, 2022)
Background Coronavirus Disease 2019 (COVID-19) is widespread among adolescents and young adults across the globe. The present study aimed to compare inflammatory markers, pulmonary function and clinical symptoms across non-hospitalized, 12 – 25 years old COVID-19 cases and non-COVID-19 controls, and to investigate associations between inflammatory markers, clinical symptoms, pulmonary function and background variables in the COVID-19 group. Methods The present paper presents baseline data from an ongoing longitudinal observational cohort study (Long-Term Effects of COVID-19 in Adolescents, LoTECA, ClinicalTrials ID: NCT04686734). A total of 31 plasma cytokines and complement activation products were assayed by multiplex and ELISA methodologies. Pulmonary function and clinical symptoms were investigated by spirometry and questionnaires, respectively. Results A total of COVD-19 cases and 111 non-COVID-19 controls were included. The COVID-19 group had significantly higher plasma levels of IL-1β, IL-4, IL-7, IL-8, IL-12, TNF, IP-10, eotaxin, GM-CSF, bFGF, complement TCC and C3bc, and significantly lower levels of IL-13 and MIP-1α, as compared to controls. Spirometry did not detect any significant differences across the groups. IL-4, IL-7, TNF and eotaxin were negatively associated with female sex; eotaxin and IL-4 were positively associated with age. Clinical symptoms were positively associated with female sex and age, but not with objective disease markers. Conclusions Among non-hospitalized adolescents and young adults with COVID-19 there was significant alterations of plasma inflammatory markers in the subacute stage of the infection. Still, pulmonary function was normal. Clinical symptoms were independent of inflammatory and pulmonary function markers, but positively associated with age and female sex.